Foreign bodies in the ear, nose and throat: an experience in a tertiary care hospital - Parmar, Sandip M.; Gupta, Lakshay; Chaudhary, Meenu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: The aim of this study was to analyze foreign bodies in terms of type, site, age and method of removal. Methods: A prospective study was performed in the department of ENT, head and neck surgery in the tertiary care hospital of Muzaffarnagar medical college, Muzaffarnagar, UP. The study population includes the number of patients with ENT FB lodgment who presented in the outpatient department or in the Casualty room during the 1-year study period (June 2021 to May 2022). Results: A total of 83 patients had FBs in the ear, nose, or throat during the study period. Of the 83 patients, 38 (45.7%) had FB in the ear, 31 (37.34%) in the nose, and 14 (16.8%) in the throat. The FB was animate (living) in 11 (28.9%) patients with FB in the ear and 02 (6.45%) patients with FB in the nose. The FB was inanimate (non-living) in 14 (100%) patients with FB in the throat, in 27 (71.05%) patients with FB of the ear, and in 29 (93.54%) patients with FB of the nose. The FB was removed with or without local anesthesia in 66 (79.51%) patients, only 17 (20.48%) patients required general anesthesia. The most common age group affected was <10 years. Conclusions: The ear was the most common site for foreign bodies in young children followed by the nasal foreign bodies and throat (esophageal>inhaled) foreign bodies.